1983
DOI: 10.1021/jo00159a016
|View full text |Cite
|
Sign up to set email alerts
|

Photodimerization of coumarins in micelles: limitations of alignment effect

Abstract: Longicaudatine has strong reserpine-like activity, which is different from the activities described by Sandberg et al.18 for fractionated extracts of S. longicaudata. Experimental SectionLongicaudatine (1): mp 350 °C dec; [a]D +141°( c 0.5, CHC13); UV 223 nm (log t 4.66), 270 (sh), 284 (4.28), 290 (4.26), 307 (sh, 3.97); in perchloric acid a strong absorption maximum appears at 268 nm; IR (KBr) 3420, 2900,1630,1600,1480, 740 cm"1. The 400-MHz 1H NMR spectrum was recorded in CDC13 on material containing 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
4

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 0 publications
1
25
0
4
Order By: Relevance
“…The chemical shifts belonging to the cyclobutane protons and cyclobutane methyl protons were visible at 3.41 and 1.41 ppm (see Supporting Information for 1 H NMR spectra). 1 H NMR spectra further confirmed the formation of primarily the syn head–tail product with minor quantities of the anti head–tail conformation, which is in agreement with previous reports [23, 24] …”
Section: Resultssupporting
confidence: 91%
“…The chemical shifts belonging to the cyclobutane protons and cyclobutane methyl protons were visible at 3.41 and 1.41 ppm (see Supporting Information for 1 H NMR spectra). 1 H NMR spectra further confirmed the formation of primarily the syn head–tail product with minor quantities of the anti head–tail conformation, which is in agreement with previous reports [23, 24] …”
Section: Resultssupporting
confidence: 91%
“…[8] The transition moments can further be influenced by solvent polarity [11] and the use of cyclodextrin or micelles. [12,15,16] With respect to previous reports, [30±34] we set forth the design and subsequent synthesis of a template, which Scheme 1. Schematic representation of the reaction pathway responsible for selective syn photodimer formation within a supramolecular 2:1 species.…”
Section: Resultsmentioning
confidence: 99%
“…Under typical experimental conditions, however, the two syn (2 A and 2 B) photoproducts are formed predominately, while only trace amounts of the anti dimers 2 C and 2 D are observed. [7] The ratio of coumarin photoproducts can significantly be altered through control of the reaction conditions such as solvent choice, [9,11,12] Lewis acid addition, [13,14] micellar environment, [15,16] solid-state irradiation, [13,14] modification of the coumarin precursor, [17,18] use of inclusion complexes [15] and tethered precursors, [17, 19±21] or recently with pseudo-rotaxanes. [22] Much effort has been focused on crystal engineering and packing within the solid state to influence the product distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] For this purpose, various media such as zeolites, clays, crystals, cyclodextrins, cucurbiturils, calixarenes, micelles, dendrimers, polymers, host-guest complexes and natural proteins have been successfully explored during the last few decades. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These studies have clearly shown that the confinement and weak interactions provided by a host can steer reactivity of guest molecules resulting in highly selective reactions that are otherwise challenging in isotropic media. Reactions of a guest molecule in confined spaces could be visualized to occur within a 'reaction cavity' with a defined boundary and some amount of 'free space' surrounding the reactant within the cavity.…”
Section: Introductionmentioning
confidence: 99%